2008
DOI: 10.1088/0957-0233/20/1/015202
|View full text |Cite
|
Sign up to set email alerts
|

An integrated interface circuit with a capacitance-to-voltage converter as front-end for grounded capacitive sensors

Abstract: This paper presents the analysis and design of an integrated interface for grounded capacitive sensors. To reduce the effects of parasitic cable capacitances, a feedforward technique has been applied. In combination with the use of a special front-end amplifier this yields high immunity for a parasitic cable capacitance. The major nonidealities of the interface circuit have been analyzed. The complete interface has been designed and implemented as an integrated circuit, using standard 0.7 μm CMOS technology. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Depending on how the capacitive sensor is connected to the electronic interface circuit, the interface principles can be categorized as (1) capacitive sensors with a grounded target electrode [9][10][11][12][13] ; (2) capacitive sensors with an active target electrode [14][15][16][17][18][19][20][21][22] ; and (3) capacitive sensors with a floating target electrode. 23,24 It should be mentioned that in all categories, to reduce external interference, the sensor plates need to be connected to the interface via a shielded cable.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Depending on how the capacitive sensor is connected to the electronic interface circuit, the interface principles can be categorized as (1) capacitive sensors with a grounded target electrode [9][10][11][12][13] ; (2) capacitive sensors with an active target electrode [14][15][16][17][18][19][20][21][22] ; and (3) capacitive sensors with a floating target electrode. 23,24 It should be mentioned that in all categories, to reduce external interference, the sensor plates need to be connected to the interface via a shielded cable.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Several solutions for interfaces with a grounded capacitive sensor have been proposed. [9][10][11][12][13] In the papers referenced, it has been shown that the use of a switched-capacitor-based approach improves the stability of the active guarding, significantly. However, not much research has been conducted yet on the effect of switched-capacitor active guarding on systematic errors and absolute accuracy with grounded capacitive sensor interfaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations